Low-threshold CMOS Rectifier Design for Energy Harvesting in Biomedical Sensors - Yuce, Mehmet; Mohammadi, Ali; Redoute, Jean-Michel (EAI Endorsed Transactions on Pervasive Health and Technology, 2015)
The power transfer efficiency of energy harvesting systems is strongly dependent on the power conditioning circuits, especially rectifiers. The voltage drop across rectifier and its leakage current can drastically influence the efficiency. The hybrid energy harvesters impose even more severe constraints on the rectifier. The low Vth transistors and bulk regulation technique are used in this work to mitigated the voltage drop and leakage current, respectively. It has been shown that the bulk regulation stops the current leakage through body of PMOS transistor. A near zero threshold cross connected CMOS rectifier is presented in this work using the standard 180nm UMC technology and experimental analysis are carried out to evaluate the circuit performance.
Keywords: hybrid energy harvesting; cmos rectifier